EARLY PLIOCENE BARB (TELEOSTEI, CYPRINIDAE, BARBINAE) FROM THE CAMP DELS NINOTS SITE (SPAIN) - Tomáš Přikryl; HUGUES-ALEXANDRE BLAIN; ORIOL OMS; PABLO RODRÍGUEZ-SALGADO; ELENA MORENO RIBAS; JORDI AGUSTÍ; GERARD CAMPENY; BRUNO BRUNO GÓMEZ DE SOLER (Rivista Italiana di Paleontologia e Stratigrafia)
The Pliocene site of Camp dels Ninots (Caldes de Malavella, NE Spain) is considered a Konservat-Lagerstätte due to the remarkable preservation of its macro and microvertebrate record, along with floral remains such as leaf imprints and seeds. Its lacustrine deposits, dated from the early Pliocene, have provided a number of semi-articulated and isolated remains of middle to large sized cyprinid fish, apparently belonging to subfamily Barbinae. These specimens allow recognize number of skeletal characters, including specific morphology of the pharyngeal dentition and denticulation at the posterior side of the last unbranched dorsal fin ray. The latter character is well discernable in smaller individuals, while in the larger specimens the denticulation is lost. These features, together with general osteological characterization, allow to classify the specimens under consideration to the species Luciobarbus graellsii (Steindachner, 1866), or closely related form morphologically non discernable from the latter. Fish of the Luciobarbus graellsii species is typical native barb inhabitant of North-Eastern Iberian Peninsula and Camp dels Ninots documents its first and earliest fossil record. Inferences for the Pliocene palaeogeography of the region as well as the palaeoecology of the species is discussed. This new fossil record enlarges the known climatic requirements of the species (as it manage to survive from the warmest period of the Pliocene to the coldest period of the Pleistocene) and documents their early abilities to disperse in peculiar aquatic environment (i.e., maars). Brief overview of the fossil record barbs from Central, Western and Southern Europe is provided.